2022
DOI: 10.3329/taj.v35i1.61135
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Myocardial Performance Indexing Assessing Acute Right Ventricular Infarction

Abstract: The goal of this study was to determine the sensitivity and specificity of the Myocardial Performance Index (MPI)for the assessment of acute right ventricular Infraction. This was a descriptive type of cross-sectional study. The study was carried out in the Coronary Care Unit, Department of Cardiology, Sir Salimulla Medical College, and Mitford Hospital. After exclusion total of 72 patients were included in this study, of which 24 had acute inferior MI with RV involvement diagnosed by ≥ 1mm ST-segment elevatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…ROC analyses demonstrated that RVESV and RVEDV had good sensitivity and specificity in predicting RV dysfunction, in agreement with the results of two previous studies. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…ROC analyses demonstrated that RVESV and RVEDV had good sensitivity and specificity in predicting RV dysfunction, in agreement with the results of two previous studies. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%